Tobacco harvesting ceremony on Merapi mountainsides as a preservation of cultural values and Javanese inheritance: critical discourse analysis - Ani Rakhmawati; Fajar Nur Anisa; Muhammad Aditya Wisnu Wardana (Cogent Arts & Humanities)
Indonesia is a country with a diversity of cultures and ethnicity. Each region has a unique culture. Thereby, preserving local wisdom is a must in enriching the culture and human nobility. The Tungguk Tobacco is one of the sacred rituals for people at the Merapi mountainsides, Boyolali Regency, as a beginning season of tobacco harvesting. This research used qualitative descriptive approach that is intended to investigate a condition, situation, and another event in the harvesting ceremony where the results are presented as a research report. This research was conducted in Selo District, Boyolali Regency, during the Tungguk Tobacco harvesting traditional ceremony activities and series of ritual events. The detailed results obtained for the subthemes are interrelated. These subthemes include gunungan a mountain or stack of tobacco and agricultural products, the Javanese symbolism of Tungguk Tobacco, and traditional art performances that met the requirements of TVD model analysis.